1994
DOI: 10.1148/radiology.193.1.7916467
|View full text |Cite
|
Sign up to set email alerts
|

Active pulmonary tuberculosis in patients with AIDS: spectrum of radiographic findings (including a normal appearance).

Abstract: Chest radiographs did not suggest active tuberculosis in 43 (32%) of 133 AIDS patients with active pulmonary tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
3
10

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(112 citation statements)
references
References 0 publications
10
89
3
10
Order By: Relevance
“…All patients with CD4+ T-lymphocyte counts < 200 cells/mm 3 presented radiological patterns that were different from the post-primary ones. These results are in accordance with other studies, where cavitation 19 20 , post-primary or typical tuberculin radiological patterns 9 were correlated with CD4+ T-lymphocyte counts > 200 cells/mm 3 and lymphadenopathy and atypical findings with lower counts 9 19 20 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All patients with CD4+ T-lymphocyte counts < 200 cells/mm 3 presented radiological patterns that were different from the post-primary ones. These results are in accordance with other studies, where cavitation 19 20 , post-primary or typical tuberculin radiological patterns 9 were correlated with CD4+ T-lymphocyte counts > 200 cells/mm 3 and lymphadenopathy and atypical findings with lower counts 9 19 20 .…”
Section: Discussionsupporting
confidence: 93%
“…Normal radiography of the thorax may be present in 5% to 10% of HIV-positive patients 8 and in up to 20% of the patients with an advanced level of immunodepression 9 . It remains uncertain whether the absence of findings represents early stages of either primary disease or reactivation, or disease caused by intrathoracic adenopathy that has not been detected by simple radiographic examination 20 .…”
Section: Discussionmentioning
confidence: 99%
“…HIV/AIDS epidemic has considerably increased the incidence of middle and lower lung field tuberculosis (LLF TB) which is frequently associated with negative sputum smear because of lower bacillary load. [2] LLF TB is defined [3] as "tuberculosis disease found below an imaginary line traced across the hila and including the parahilar regions on a standard posterior-anterior chest roentgenogram." Ossen [4] subdivided his cases into pure and impure groups: the pure group has no visible lesions in the upper lung fields and the impure group has nodular or fibrotic infiltrations in one or both apices.…”
Section: Introductionmentioning
confidence: 99%
“…et al [2] in their study of chest radiograph of 133 adult patients with AIDS observed the following pattern. IJBR (2015) 6 (08) www.ssjournals.com…”
Section: Discussionmentioning
confidence: 87%